Analisis Penggunaan Kamus dalam Penguasaan Kosakata Bahasa Arab Peserta Didik di kelas XI MIA di MA Al-Muthohhar - Dede Rizal Munir; Ali irfan (JURNAL ILMIAH RESEARCH STUDENT, 2023)
. One of the challenges in developing Arabic language teaching in Indonesia is the low interest of students in opening a dictionary. This research aims to analyze the use of dictionaries in mastering Arabic vocabulary by class XI MIA students at MA Al-Muthohhar. This research was conducted to understand the extent to which dictionaries are used as an aid in improving students' Arabic vocabulary skills at the secondary education level. The research method used was a descriptive method with data collection through questionnaires distributed to class XI MIA students. The questionnaire was designed to measure the extent to which students use dictionaries in their Arabic language learning and whether the use of dictionaries has a positive impact on their mastery of Arabic vocabulary. The results of the research show that the majority of class XI MIA students at MA Al-Muthohhar use a dictionary as a tool in understanding Arabic vocabulary. These results also indicate that the use of a dictionary has a positive impact on students' mastery of Arabic vocabulary. Thus, the use of a dictionary can be considered as an effective strategy in learning Arabic at the secondary school level. This research is expected to provide better insight into the use of dictionaries in Arabic language learning in the secondary school environment. The implication of this research is the importance of encouraging students to use dictionaries as a tool in enriching their vocabulary in Arabic. Apart from that, this research can also be a guide for Arabic teachers in designing more effective teaching methods to improve students' ability to master Arabic vocabulary.